General practitioner workforce sustainability to maximise effective and equitable patient care: a realist review protocol - Claire Goodman; Sophie Park; Geoff Wong; Gillian Vance; Bryan Burford; Margaret Ogden; Tim Rapley; Claire Duddy; Emily Owen-Boukra; Tanya Cohen; Harry Dunn; Vacha Fadia; et al. (BMJ Open, 2024)
Introduction There are not enough general practitioners (GPs) in the UK National Health Service. This problem is worse in areas of the country where poverty and underinvestment in health and social care mean patients experience poorer health compared with wealthier regions. Encouraging more doctors to choose and continue in a GP career is a government priority. This review will examine which aspects of the healthcare system affect GP workforce sustainability, how, why and for whom.Methods and analysis A realist review is a theory-driven interpretive approach to evidence synthesis, that brings together qualitative, quantitative, mixed-methods research and grey literature. We will use a realist approach to synthesise data from the available published literature to refine an evidence-based programme theory that will identify the important contextual factors and underlying mechanisms that underpin observed outcomes relating to GP workforce sustainability. Our review will follow Pawson’s five iterative stages: (1) finding existing theories, (2) searching for evidence, (3) article selection, (4) data extraction and (5) synthesising evidence and drawing conclusions. We will work closely with key stakeholders and embed patient and public involvement throughout the review process to refine the focus of the review and enhance the impact and relevance of our research.Ethics and dissemination This review does not require formal ethical approval as it draws on secondary data from published articles and grey literature. Findings will be disseminated through multiple channels, including publication in peer-reviewed journals, at national and international conferences, and other digital scholarly communication tools such as video summaries, X and blog posts.PROSPERO registration number CRD42023395583.